2023
DOI: 10.1002/pros.24558
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of simultaneous integrated boost to intraprostatic lesions with external beam radiotherapy in localized prostate cancer patients

Abstract: Background To evaluate the treatment outcomes and toxicity of definitive radiotherapy (RT) for prostate cancer (PC) patients using the simultaneous integrated boost (SIB) technique, which delivered 78 Gy to the entire prostate and 86 Gy to the intraprostatic lesion (IPL) in 39 fractions. Materials and Methods Univariable and multivariable analyses were conducted of the prognostic factors for freedom from biochemical failure (FFBF), progression‐free survival (PFS), and PC‐specific survival (PCSS) of 619 PC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The recent randomized FLAME trial found that adding a focal boost to the IPL in patients with intermediate‐ and high‐risk prostate cancer improved the bDFS rate without any negative impact on toxicity or quality of life 12 . In a similar fashion, we demonstrated that localized PC was successfully and safely treated with definitive RT using the SIB technique to deliver 86 Gy to the IPL in 39 fractions without severe late toxicity 13 …”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…The recent randomized FLAME trial found that adding a focal boost to the IPL in patients with intermediate‐ and high‐risk prostate cancer improved the bDFS rate without any negative impact on toxicity or quality of life 12 . In a similar fashion, we demonstrated that localized PC was successfully and safely treated with definitive RT using the SIB technique to deliver 86 Gy to the IPL in 39 fractions without severe late toxicity 13 …”
Section: Introductionsupporting
confidence: 59%
“…All patients received 78 Gy for their prostate and the proximal portion of the seminal vesicles, while patients receiving FB received 86 Gy to IPL using the SIB technique. Until 2012, the prescribed dose to the prostate was 78 Gy, but as of 2012, the treatment protocol has been modified to include a FB to the IPL 13 . No patients received pelvic lymph node irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical target volume included the prostate and the proximal two thirds of the seminal vesicles. The planning target volume for the prostate was determined by adding a 5-mm posterior margin to the clinical target volume, with an 8-mm margin in all other directions 16,17 . The pelvic nodal area was defined according to Radiation Therapy Oncology Group guidelines, 18 except that the pelvic field extended superiorly from L4/L5 to cover the proximal common iliac lymph nodes 19 …”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated the dosimetric feasibility of delivering 78 Gy to the entire prostate and 86 Gy to IPL using the SIB technique delivered in 39 fractions [9], and we routinely employ this technique in clinical practice [26]. Literature data suggest that 36.25 Gy is an appropriate dose to avoid urinary side effects, but it may not be sufficient to ensure proper local control, particularly for prostate cancer with a high-to-intermediate risk.…”
Section: Introductionmentioning
confidence: 99%